New Approaches to Molecular Profiling of Tissue Samples - Carolyn J. M. Best; John W. Gillespie; Chad R. Englert; Jennifer I. Swalwell; John Pfeifer; David B. Krizman; Emanuel F. Petricoin; Lance A. Liotta; Michael R. Emmert-Buck (Analytical Cellular Pathology)
Figures on http://www.esacp.org/acp/2000/20-1/best.htm.